2018
DOI: 10.7287/peerj.preprints.27245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biochemical analysis and comparative studies on Diospyros kaki extracts

Abstract: Background: Limited study on different organs of Diospyros kaki in biochemical figure of Pakistani plants still require considerable research activities due to its remarkable antioxidant properties. Objective: This study was an effort to characterize antioxidant properties regarding Diospyros kaki with special reference to its detailed biochemical analysis and linked health claim. Method: The biochemical analysis according to the role of certain bioactive molecules in different plant organs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The decoction with 1000 µg/mL showed the greatest inhibition rate of 79.42±1.45% which was lower than those of Diclofenac sodium (standard drug) with 93.33±1.53%. This anti-inflammation power of C. americanum extract could be due to the presence of bioactive compounds including alkaloids, flavonoids, saponins, tannins, terpenoids and phenolic compounds [26]. Indeed, Yui et al [27] reported that the alkaloids would inhibit TNF-α production either by inhibiting protein synthesis or by altering cysteine/methionine incorporation in macrophages [27].…”
Section: Effect Of Protein Denaturationmentioning
confidence: 99%
“…The decoction with 1000 µg/mL showed the greatest inhibition rate of 79.42±1.45% which was lower than those of Diclofenac sodium (standard drug) with 93.33±1.53%. This anti-inflammation power of C. americanum extract could be due to the presence of bioactive compounds including alkaloids, flavonoids, saponins, tannins, terpenoids and phenolic compounds [26]. Indeed, Yui et al [27] reported that the alkaloids would inhibit TNF-α production either by inhibiting protein synthesis or by altering cysteine/methionine incorporation in macrophages [27].…”
Section: Effect Of Protein Denaturationmentioning
confidence: 99%